Ruminal and intestinal nylon bag degradation of cell wall constituents of grass silages preserved with different additives - Vanhatalo, A.; Varvikko, T.; Aronen, I. (IAEA, 1991)
The effect of ensiling additives on ruminal and intestinal nylon bag degradation of grass silage cell wall constituents was studied. Herbage consisting of Dactylus glomerata and Phleum pratense was ensiled with the following commercial additives in small scale silos of 3m3. 1) AIV-2 containing 80 percent formic acid and 2 percent orthophosphoric acid (5.5 2/t); (2) Ensimax containing 50 percent Finfermex solution, 25 percent formic acid, 15.5 percent acetic acid and 9.5 percent hydrochloric acid (5.6 L/t); (3) Clampzyme containing cellulase and glucose oxidase (200 mL/t) and (4) without additives. The difference for cell wall constituents was most probably due to too short an incubation time in the rumen (30h) used with the nylon bag technique compared with the actual retention time of the cell wall fractions of 50-60 h, obtained on the respective grass silage diets. However the methods used gave a similar order of digestibility of feeds, so that the cell wall digestibility of C was lowest with both methods.